An evidence-based self-management package for urinary incontinence in older women: a mixed methods feasibility study - Yu Fu; E. Andrea Nelson; Linda McGowan (BMC Urology, 2020)
Abstract Background Urinary incontinence (UI) is a distressing condition that limits women’s quality of life and places a heavy burden on health care services. Behavioural treatments are recommended as a first-line treatment. An evidence-based self-management package was developed following the Medical Research Council (MRC) framework for complex interventions. This study aimed to evaluate the feasibility and acceptability of the intervention. Methods A mixed-methods approach was undertaken, namely a randomised controlled feasibility study with nested qualitative study. Fifty women aged 55 or over living with UI, recruited from community centres were randomly assigned to either a 3-month course with the package with a support session or a control group to receive the same package only 3 months later. Principal outcome measures were: self-reported quality of life, UI severity, self-efficacy and psychological status. Analysis of covariance was undertaken to estimate within- and between- group changes for all outcomes. Acceptability was explored using individual interviews at follow-up. Results Fifty women were randomised (24 to intervention, 26 to control); mean age of 69.7 (±9.1) years and mean UI frequency 2.2 (±2.2) episodes/day at baseline. Overall, 49 women (98%) completed 3-month follow-up (24 in the intervention, 25 in the control). A positive trend was detected in the impact of UI on their personal relationships (− 3.89, p = 0.088), symptom severity (− 1.77, p = 0.025), UI symptoms scale (− 1.87, p = 0.031) and anxiety status (− 2.31, p = 0.001), respectively. Changes in quality of life and self-efficacy did not differ significantly between groups. Majority of women (71%) in the intervention group reported subjective improvement after 3 months. Spearman correlation coefficient was 0.43 (p < 0.05) between their subjective perception of change and self-efficacy. Women perceived the package being acceptable and described that the package had the potential to increase their knowledge and confidence to manage symptoms and improve quality of life. Conclusions The study demonstrated that the self-management package is feasible and acceptable for older women with UI. Further studies are needed with a large sample size in clinical settings to evaluate the effectiveness of this package. Trial registration ISRCTN17194896 . Registered on 11th September 2019 (retrospectively registered).